Digital technologies as solutions to China’s aging population: a systematic review of their opportunities and challenges in rural development - Yue Ming; Yimin Li; Yun Liu (Frontiers in Public Health)
IntroductionDifferences exist in the rate of aging between individuals residing in urban and rural areas in China, with rural areas experiencing a more pronounced impact. Smart aging represents a prevalent future trend in this regard, though its development will inevitably face challenges. However, studies focusing on rural areas are scarce. Future models of aging in less developed regions, including rural areas and townships, are expected to integrate and draw inspiration from the smart aging paradigm.MethodsWe present a systematic review of the current application of digital technologies in caring for older people in rural areas. We conducted extracted and screened 26 articles out of 823, sourced from five databases: Web of Science, IEEE Xplore, Engineering Village, PubMed/MEDLINE and CNKI.ResultsThe articles focus on digital technologies that cater to the daily life, medical care, spiritual comfort, and cultural entertainment needs of rural older people. In our review, we focused on four aspects of digital technology: mobile applications (apps), websites and platforms, mobile devices and terminals, and VR technologies or other unspecified technologies.DiscussionWe found that current digital technologies for smart aging have room for improvement in meeting the recreational and mental comfort needs of older adults. Digital technologies are predominantly applied to the smart community/rural and smart healthcare sectors, with limited applications in the smart home sector. Future studies should explore smart-home older adults care services to address digital cognitive barriers faced by older adults.